PENGARUH PEMERIKSAAN PAJAK TERHADAP KEPATUHAN WAJIB PAJAK DAN DAMPAKNYA TERHADAP EFEKTIVITAS PENERIMAAN PAJAK PENGHASILAN BADAN - RW, Neng Siti; Bagianto, Agus; Yuniati, Yuniati (2018)
Human resources are a supporting factor for companies to survive in competition. Compensation plays an important role in improving employee performance, one of the main reasons a person works is to make ends meet. Someone will work maximally to get the compensation in accordance with expectations. The compensation policy in addition to rewarding employees for the work performed by employees is also one way to retain potential employees. Based on the variables studied, the research method used in this research is descriptive and associative method. Descriptive research is a study conducted to determine the value of independent variables and does not make the comparison of variables with other variables Descriptive research here aims to obtain a picture of direct compensation, indirect compensation and employee performance at PT Pranata Jaya Abadi. While the method of associative research is research that aims to determine the influence or also the relationship between two variables or more. The results of this study show a multiple linear regression equation as follows: Y = 0.414 + 0.997X1 + 0.866X2, which can be interpreted as that the variables X1 and X2 are zero (0), then the variable Y will be worth 0.414 units; if the direct compensation (X1) increases by one unit and the other variable is constant, then the Y variable will increase by 0.997 units, and if the indirect compensation (X2) increases by one unit and the other variable is constant, then the Y variable will increase by 0.866 units. The conclusion of this study obtained the value of determination coefficient of 82.7% or the value of 0.827 which indicates the meaning that direct compensation (X1) and indirect compensation (X2) gives simultaneous effect of 82.7% on employee performance (Y ). While the rest of 17.3% influenced by other factors that ignored the author. The value of Adjusted R2 0.820 or the value of 82.0% indicating the meaning that, if there are other independent variables to be included, direct and indirect compensation variables, remain to have an effect of 82.0%. Against employee performance.